Case Report: BCG-Triggered Hemophagocytic Lymphohistiocytosis in an Infant With X-Linked Recessive Mendelian Susceptibility to Mycobacterial Disease Due to a Variant of Chronic Granulomatous Disease - Al-Hammadi, Suleiman; Yahya, Amal M.; Al-Amri, Abdulla; Shibli, Amar; Balhaj, Ghazala B.; Tawil, Mohamed I.; Vijayan, Ranjit; Souid, Abdul-Kader (Frontiers in Pediatrics, 2021)
In the United Arab Emirates, BCG (Bacillus Calmette-Guérin) is administered to all newborns. We present here a young infant with an inborn error of immunity (IEI) who developed fatal adverse events to this live-attenuated vaccine. This male infant received BCG (Serum Institute of India PVT, LTD; India) on Day 11 of life. On Day 25, he developed fever, followed by cervical lymphadenitis and bilateral otitis media with fluid drainage. On Day 118, he was admitted with severe hemophagocytic lymphohistiocytosis (HLH), and passed away on Day 145. The diagnostic exome sequencing test identified a hemizygous nonsense variant, NM_000397.3(CYBB):c.676C>T, p.Arg226* (rs137854592). Pathogenic variants of CYBB [cytochrome b(-245), beta subunit; Mendelian Inheritance in Man [MIM] accession code, 300481] are known to cause ‘immunodeficiency 34, mycobacteriosis, X-linked’ (IMD34, MIM#300645) and ‘chronic granulomatous disease, X-linked’ (CGDX, MIM#306400). The natural history of his illness is consistent with ‘X-linked recessive Mendelian susceptibility to mycobacterial disease (MSMD)’. This entity is responsible for his BCG disease, and is a likely trigger of his HLH. This disastrous event underlines the importance of developing worldwide policies that target BCG disease prevention, especially in communities with high prevalence of IEI. Moreover, screening for genetic causes of MSMD in the community could pave the way, at least partially, for scale-up of tuberculosis (TB) prevention.